Performance of High-Gain Observer (HGO) For Level Estimation in Continuous Stirred Tank Reactor (CSTR) - Dian Mursyitah; Ahmad Faizal; Zulfatri Aini (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
This paper presents an estimation of level in CSTR system. Due to the non-linearity in the model of the CSTR system, our focus is on observers capable of handling this non-linearity. We proposed to use a High Gain Observer (HGO) for performing level estimation. The desired characteristics for estimation include minimal error, fast convergence time, and robustness in the presence of noisy measurements. A comprehensive analysis of the observers, including the evaluation of their effectiveness and robustness, is presented through simulation